TᾹJUL LUGHATI: DESAIN MEDIA PEMBELAJARAN ONLINE - Mabruroh, Hani'atul; Subakir, Fairuz; Nurlaila, Riza; Syammary, Naufal Akmal (STIQ Amuntai, 2021)
This study aims to provide Arabic language learning solutions based on the website that can be applied in Arabic language learning during the covid-19 pandemic. This is based on Arabic language learning for students in UNIDA Gontor schools experiencing decreased quantity and quality. The long-lasting pandemic resulted in Pusdiklat UNIDA Gontor vacuum from training for MTS equivalent at home or abroad. Therefore, website-based online learning is expected to provide solutions for Arabic language learning in the pandemic. This research uses the early stage of the Research and Development method, where the process stops at product design without conducting trials of the product. This research data was obtained by observation, interview, questionnaire, and literature study. The result of this study is in the form of Arabic language learning media based on a website called